Empirical Investigation of Empowerment among Underprivileged Women through Livelihood Strategies in South Punjab, Pakistan - Moiza Saleem; Dr. Farah Riaz; Dr. Muhammad Iqbal Zafar* (Journal of Religion and Society, 2025)
This study investigates the complex relationship between structured livelihood strategies and the multidimensional empowerment of underprivileged women in South Punjab, Pakistan. The research is situated within the context of profound gender disparities and economic marginalization, examining whether interventions such as microfinance, vocational training, and agricultural innovation catalyze tangible improvements in women's economic independence, decision-making autonomy, and community participation. The core objectives were to assess the demographic and socio-economic profile of underprivileged women in the region, to analyze the individual and combined impact of specific livelihood strategies on key empowerment indicators, and to identify the constraining role of entrenched gender norms and cultural barriers. A quantitative, cross-sectional methodology was employed, utilizing a structured interview schedule administered to a systematically selected sample of 500 women across the districts of Multan, Khanewal, and Bahawalpur. The data was analyzed using SPSS version 24.0, incorporating descriptive statistics and Pearson correlation analysis. The results reveal that vocational training and microfinance access demonstrate significant positive correlations with all empowerment domains, with training showing particularly broad-based efficacy.. The findings indicate that while targeted livelihood interventions are potent tools, their empowerment outcomes are deeply contingent upon the socio-cultural ecosystem, suggesting that integrative approaches addressing both economic and normative structures are essential for transformative change. Keywords: Women’s Empowerment, Livelihood Strategies, Microfinance, Vocational Training, South Punjab, Gender Norms, Economic Independence.